2007
DOI: 10.1680/gein.2007.14.6.330
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of reinforced soil-retaining wall structures with cohesive and granular backfills

Abstract: The failure mechanisms of reinforced soil segmental walls with extensible reinforcements were studied by performing a numerical analysis using the finite element method. The numerical approach was first verified against the results of three instrumented full-scale structures reported in the literature. Finite element models with different combinations of reinforcement spacing, reinforcement length and backfill soil were analysed. The ϕ–c reduction method, which is a special shear strength parameter reduction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(39 citation statements)
references
References 9 publications
1
35
0
3
Order By: Relevance
“…Ling and Leshchinsky [5], Hatami and Bathurst [7,8] and Guler et al [9] verified their numerical models against carefully constructed, instrumented and monitored walls. Reviews of numerical modelling of geosynthetic reinforced soil wall can be found in the papers by Bathurst and Hatami [10] and Ling [11].…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Ling and Leshchinsky [5], Hatami and Bathurst [7,8] and Guler et al [9] verified their numerical models against carefully constructed, instrumented and monitored walls. Reviews of numerical modelling of geosynthetic reinforced soil wall can be found in the papers by Bathurst and Hatami [10] and Ling [11].…”
Section: Introductionmentioning
confidence: 93%
“…8 Comparison of stress-strain curves of WGT reinforced sand (RD-40 %, r 3 -50 kPa) based on equivalent and discrete approach Fig. 9 Comparisons of stress-strain curves of WGT reinforced sand (RD-40 %, r 3 -50 kPa) using Mohr-Coulomb and Duncan-Chang model scale geogrid reinforced retaining wall constructed at Royal Military College of Canada (RMC) [7,8] and a reinforced retaining wall problem analysed by Guler et al [9] were analysed using FLAC. The equivalent numerical model is systematically verified with the instrumented data together with results from discrete approach.…”
Section: Case Studiesmentioning
confidence: 99%
See 3 more Smart Citations